the THE INFLUENCE OF PERCEIVED PRODUCT QUALITY AND PERCEIVED SERVICE QUALITY TOWARD CUSTOMER VALUE, BEHAVIOR INTENTION AND CUSTOMER RESPONSE RESIDENTIAL AREA IN SOUTH KALIMANTAN PROVINCE - sutrisno, (Archives of Business Research, 2019)
ABSTRACT The research aims to analyze the influence of Perceived Product Quality And Perceived Service Quality Toward Customer Value, Behavior Intention And Customer Response Residential Area In South Kalimantan Province. The population in this research is the customer Residential Area In South Kalimantan Province. Sampling technique by using accidental sampling with selected respondents must meet predetermined criteria standards. because the population is very much. The number of samples as many as 120 responden, this was according to Ferdinand (2002:48). The analysis was using SPSS and using AMOS 20.0 software. The test results showed that only six hypothesis have a significant effect, namely: Perceived product quality significantly influence toward customer value in Residential Area In South Kalimantan Province, Perceived service quality significantly influence toward customer value in Residential Area In South Kalimantan Province, Perceived product quality significantly influence toward behavior intention customer in Residential Area In South Kalimantan Province, Perceived service quality significantly influence toward behavior intention customer in Residential Area In South Kalimantan Province, customer value significantly influence toward customer respon in Residential Area In South Kalimantan Province, customer intention significantly influence toward customer respon in Residential Area In South Kalimantan Province. While three other hypothesis have not significant namely: customer value have not significant influence to customer intention in Residential Area In South Kalimantan Province, perceived product quality have not significantly influence to customer response in Residential Area In South Kalimantan Province and perceived service quality have not significant influence toward customer response in Residential Area In South Kalimantan Province. Keywords: Product Quality, Service Quality, Customer Value, Behavior Intention, Customer Response